Determination of yield and some quality traits of Pistachio cv. ‘Siirt’ trained different systems - Aktug Tahtaci S.; Gozel H.; Yilmaz A.; Ak B.E. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Pistachio trees grow under sunny and hot areas, for preventing those damages and circulation, it is needed a good shaped tree crown. This just can be done after planting with each year regular pruning. There is not much more studies on this matter. It is unknown how to effect training systems to yield and quality. Via a good training system and pruning that is made for physicological base of tree, yield can be separated in each year production. This study was started in 1995 to determine the best training system to get high yield and having more quality. Three (The Open-Center System, Open center system closed with lateral branches and Modified Central Leader system) training systems were applied to the experimental trees. Yield and quality in cultivar ‘Siirt’ were recorded.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)